Improved cycling performance after steady state versus variable intensity exercise - Palmer, G. S.; Hawley, J. A.; Dennis, S. C.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 1996)
The effects of a single continuous bout of steady-state (SS) or variable intensity (VI) exercise on subsequent 20 km cycling time in six trained male cyclists were evaluated. Exercise bouts were 150 min in length. SS intensity was 58% of peak power output and variable work rates ranged 58+/-12.2%. A 20 km time-trial followed immediately. Heart rates did not differ during either the preliminary or time-trial rides. Peak power output was significantly higher and time-trial faster following the SS preparatory exercise. Implication: Steady-state warm-up work in cycling would be better than variable intensity riding when preparing to perform a predominantly aerobic cycling event.